A rare case report on complete cervical agenesis with vaginal atresia and suspended didelphys uterus with hematometra and left haematosalpinx - Dwivedi, Divya; Jain, Madhu; Jain, Shuchi; Jain, Shivi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Congenital uterine malformations are deviations from normal anatomy resulting due to defective fusion of Mullerian ducts or the paramesonephric ducts in the developing embryo. These anomalies may be isolated or in combination with urological abnormalities. The mean prevalence of female congenital malformations in general population is up to ⁓ 7%. Patients with these anomalies usually present during pubertal age due to absence of onset of menses, cyclical abdominal pain, or in reproductive age group as infertility or recurrent pregnancy loss depending upon the degree of malformation. Cervical agenesis is a rare Mullerian anomaly with an incidence of 1 in 80,000 females. It represents 3% of all uterine anomalies. It is rarely associated with a functioning uterus (4.8%). Cervical agenesis is often associated with vaginal atresia (less than 50%). It is important to classify these anomalies for easy diagnosis and plan appropriate preoperative treatment.